EARLY DEVELOPMENT OF CORONARY ARTERY DISEASE AT A YOUNG WOMAN - Abilmazhinova, G.D.; Mussin, A.M.; Madiyeva, M.I. (European Scientific Journal, ESJ, 2014)
The authors described a case of myocardial infarction at a young woman, which shows the influence of traditional risk factors and metabolic syndrome on the early development of coronary artery disease. Indicators of morbidity, disability and mortality due to major diseases of the circulatory system (DCS) tend to steady growth throughout the world, including Kazakhstan. Out of the total deaths worldwide DCS occupy leading positions. So according to the World Health Organization (WHO) more than 55 % of deaths and disability are caused by heart diseases. Every year the world's 17.3 million people die of cardiovascular disease, which is a leading cause of mortality among men and women. The number of deaths is projected to increase in 2030 to 23.3 million cases. Estimated at 8.6 million, including fatal cases of coronary heart disease today are women. Women under 50 who have experienced a heart attack of coronary nature are twice as likely to die than men of this age group. Women who have had a seizure at the age of 65 are more likely to die than men within a year after hospitalization: 42% versus 24%. [1]